New CNN-type ruthenium pincer NHC complexes. synthesis and catalytic activity. mild, efficient hydrogenation of esters - Fogler, Eran; Balaraman, Ekambaram; Ben-David, Yehoshoa; Leitus, Gregory; Shimon, Linda J. W.; Milstein, David (Organometallics, 2011)
New pincer ruthenium complexes (2–6) based on the new bipyridine-NHC ligand 1 were prepared and studied, resulting in an efficient catalytic hydrogenation of esters to the corresponding alcohols under mild conditions. Reaction of the ligand 1 with RuH(Cl)CO(PPh3)3, followed by reaction with one equivalent of the base KHMDS, gave the mixed phosphine-NHC complex 2, incorporating a C–H-activated bipyridine ligand. Complex 2 has an octahedral structure containing two phosphorus atoms trans to each other, a hydride trans to the NHC ligand, and CO trans to the C–H-activated carbon of the bipyridine ligand. Using the precursor complex Ru(p-cymene)Cl2(CO), reaction with 1 followed by treatment of the intermediate product with one equivalent of KHMDS resulted in formation of the dichloride pincer complexes 3a and 3b, which are in equilibrium, as indicated by variable-temperature 1H NMR. Complex 3a is an octahedral, neutral, and symmetric complex with the CO ligand positioned trans to the central pyridine group of the pincer ligand and the two chlorides trans to each other, as indicated by single-crystal X-ray diffraction. Complex 3b is cationic, with an outer-sphere chloride. Reaction of the NHC ligand 1 with LiHMDS at low temperature followed by addition of RuH(Cl)CO(PPh3)3 resulted in the mixed phosphine-NHC complex 4, which has an octahedral structure containing phosphorus trans to the hydride, a CO trans to the NHC ligand, and an outer-sphere chloride. Chloride substitution by BArF– gave the X-ray-characterized complex 5. Deprotonation of complex 4 with KHMDS resulted in formation of the dearomatized complex 6. The in situ prepared 6 (from complex 4 and an equivalent of base) is among the best catalysts known for the hydrogenation of nonactivated esters to the corresponding alcohols under mild conditions.